RESPONS PERTUMBUHAN DAN PODUKTIVITAS TANAMAN SAWI PAKCOY (Brassica rafa L.) MELALUI PENGAPLIKASIAN JENIS PUPUK ORGANIK CAIR - Agus Saleh Setiawan; Choirul Anam; Dian Eka Kusumawati (Agroteknologi Fakultas Pertanian Universitas Islam Darul 'Ulum (UNISDA), 2024)
Mustard pakcoy is one of the easiest vegetables to grow. The demand for pakcoy is increasing as the number of Indonesian people continues to grow. However, the demand for pakcoy is inversely proportional to its production in the field. Currently, farmers in Indonesia are beginning to understand the importance of using organic fertilizers in the cultivation process. In facing environmental challenges, the use of organic fertilizers is considered a more environmentally friendly alternative compared to chemical fertilizers. This research identifies types of liquid organic fertilizers (POC) that are not only effective but also contribute to environmental sustainability. It aimed to determine the response of POC application on the growth and productivity of pakcoy mustard. This study applied a one-factor Randomized Group Design method with seven levels repeated four times. The factor is the type of liquid organic fertilizer including: no treatment, Biotani Plus, Nasa, Bio Conversion, NaturGen, Eco Fresh, and Explant PHC. The research observations were plant height, number of leaves, wet weight per sample plant, wet weight per plot and wet weight per hectare. The data obtained from the observations were calculated by analyzing the Fisher's test variance at the 5% and 1% levels, if significantly different, it was continued with the 5% BNT test. From the research, it was found that the provision of POC Biotani Plus gave the best results among other types of POC on the growth and yield of pakcoy mustard greens.